2015
DOI: 10.1016/j.yhbeh.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone (DHEA) and dehydroepiandrosterone-sulfate (DHEAS) and emotional processing — A behavioral and electrophysiological approach

Abstract: Dehydroepiandrosterone (DHEA) and dehydroepiandrosterone-sulfate (DHEAS) may have mood enhancement effects: higher DHEAS concentrations and DHEA/cortisol ratio have been related to lower depression scores and controlled trials of DHEA administration have reported significant antidepressant effects. The balance between DHEAS and DHEA has been suggested to influence brain functioning. We explored DHEAS, DHEA, cortisol, DHEA/cortisol and DHEAS/DHEA ratios relations to the processing of negative emotional stimuli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The biological activity of DHEA(S) coupled with their association with cognitive function observed across various clinical populations lead us to suggest that DHEA(S) supplementation may potentially serve as a pharmacologic intervention to help with cognition in CRCI. Reports of DHEA(S) administration typically outline beneficial effects on cognition overall, with a certain specificity for working memory and attention, which may support the use of DHEA(S) supplementation as a preemptive intervention to address CRCI. To support this statement, it would be prudent to know whether patients experiencing CRCI possess low levels of DHEA(S) prior to chemotherapy treatment.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The biological activity of DHEA(S) coupled with their association with cognitive function observed across various clinical populations lead us to suggest that DHEA(S) supplementation may potentially serve as a pharmacologic intervention to help with cognition in CRCI. Reports of DHEA(S) administration typically outline beneficial effects on cognition overall, with a certain specificity for working memory and attention, which may support the use of DHEA(S) supplementation as a preemptive intervention to address CRCI. To support this statement, it would be prudent to know whether patients experiencing CRCI possess low levels of DHEA(S) prior to chemotherapy treatment.…”
mentioning
confidence: 97%
“…This is mediated by binding to brain receptors (such as the N ‐methyl d ‐aspartate and γ‐aminobutyric acid receptors) for which they have shown affinity or through the conversion into active metabolites or more potent steroid hormones such as estradiol . Although DHEA and DHEAS can be reversibly converted into each other, their molecular effects are not the same, and it is postulated that the balance between both forms influence brain functioning …”
mentioning
confidence: 99%
“…Similarly, several studies found positive correlations between DHEA(S) levels and memory functions, while identifying negative correlations between cortisol levels and memory function tasks (Carlson et al, 1999; Kalmijn et al, 1998). Supporting these findings of opposing effects of cortisol and DHEA(S) at an electrophysiological level, do Vale et al (2015) found that higher salivary cortisol levels were associated with increased distractibility, whereas higher DHEA levels were associated with less distractibility and with improved working memory in women. The relationship between DHEA(S) levels in serum and DHEA(S) levels or actions in the HC is not fully known, but these studies suggest that peripheral levels of DHEA(S) in humans may be relevant markers of HC volume, perfusion and/or function, at least in certain disease states.…”
Section: Introductionmentioning
confidence: 61%
“…The relationship between DHEA(S) levels in serum and DHEA(S) levels or actions in the HC is not fully known, but these studies suggest that peripheral levels of DHEA(S) in humans may be relevant markers of HC volume, perfusion and/or function, at least in certain disease states. Additional studies that concurrently assessed cortisol and DHEA(S) provide some preliminary evidence of interactions between cortisol and DHEA at the level of hippocampus (Carlson et al, 1999; do Vale et al, 2015; Kalmijn et al, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Basal cortisol also seems to correlate with cognitive control (Schutter and Van Honk, 2005). Few studies have took testosterone, cortisol and cognitive control processings as mechanisms underlying emotional intelligence, although there were some studies concerning other hormones and emotional perception in the context of emotional intelligence (Cardoso et al, 2014;Koven and Max, 2014;Milivojevic et al, 2014;do Vale et al, 2015). It is possible that the ratios of the basal levels of testosterone and cortisol are closely related to emotion regulation (Van Honk and Schutter, 2006).…”
Section: Introductionmentioning
confidence: 99%